Fostering medication review competence of pharmacy students: An assessment by students and their preceptors after advanced‐level practical internship - Leiman, Katja; Westerholm, Aleksi; Vahlberg, Tero; Lias, Noora; Lindholm, Tanja; Airaksinen, Marja (Wiley & British Pharmacological Society, 2026)
Aims
The aim of this study was to introduce a new assessment method for pharmacy students' real-life competence in reviewing medications after obligatory advanced-level practical internship in Finland.
Methods
The new medication review (MR) competence assessment method consisted of (1) a self-assessment by pharmacy students and (2) a performance assessment by their MR specialized preceptors at the completion of the advanced-level pharmacy internship during the third study year at the University of Helsinki, Finland. The assessment applied a structured and validated electronic evaluation tool based on national MR competence recommendations for pharmacists (31 items).
Results
Altogether 378 students and their MR preceptors assessed students' MR competence during the period of November 2020–December 2023. Majority of the students self-assessed their MR competence as very good (25%) or good (70%). Preceptors' estimates for students' MR competence were higher, as they graded 54% of the students with the grade very good and 43% with the grade good. Differences between students' and preceptors' assessments were statistically significant (p < .05) in all other statements except for ‘Understands the importance of medication reconciliation and prescription review in improving medication safety and outcomes’ (p = .829). The preceptors tended to assess students' MR competence as better than students themselves.
Conclusions
Combining self-assessment and assessment by an MR specialized preceptor forms a feasible method for assessing the real-life MR competence of students after advanced-level pharmacy internship. The involvement of the students' and preceptors' assessments can balance the effect of over- and under-estimation of the competence.